Bidirectional Resonant DC-DC converter for Microgrid Applications - Jaisudha S.; Sowmiya Srinivasan; Kanimozhi Gunasekaran (Institute of Advanced Engineering and Science, 2017)
This paper proposes a non-isolated soft-switching bidirectional dc/dc converter for interfacing energy storage in DC microgrid. The proposed converter employs a half-bridge boost converter at input port followed by a LCC resonant tank to assist in soft-switching of switches and diodes, and finally a voltage doubler circuit at the output port to enhance the voltage gain by two times. The LCC resonant circuit also adds a suitable voltage gain to the converter. Therefore, overall high voltage gain of the converter is obtained without a transformer or large number of multiplier circuit. For operation in buck mode, the high side voltage is divided by half with capacitive divider to gain higher step-down ratio. The converter is operated at high frequency to obtain low output voltage ripple, reduced magnetics and filters. Zero voltage turn-on is achieved for all switches and zero current turn-on and turn-off is achieved for all diodes in both modes i.e., buck/boost operation. Voltage stress across switches and diode is clamped naturally without external snubber circuit. An experimental prototype has been designed, built and tested in the laboratory to verify the performance of the proposed converter.